(3JCKjQ GdeMJhi GdeOQS Ydi OGaYjI GdGOGA GdegGQj GdMQcj dOi JdGejP GdeQMdI GdKGfhjI (B: (3OQGSI ejOGfjI HKGfhjI GdTgjO eQRhc OMeGf HSjOj YGeQ hdGjI GdeSjdIs - (3eSYhOj , UGdMs; (3Ndahfj, eMeO YOfGfs; (3eYgO GdJQHjI GdHOfjI h GdQjGVjI, LGeYI GdLRGFQ (B3 s ((3GdLRGFQ s, 2022)
(3JCKjQ GdeMJhi GdeOQS Ydi OGaYjI GdCOGA GdegGQj GdMQcj dOi JdGejP GdeQMdI GdKGfhjI OQGSI ejOGfjI HKGfhjI GdTgjO eQRhc OMeGf JgOa gPg GdOQGSI Gdi eYQag eOi JCKjQ GdeMJhi GdeOQS Ydi OGaYjI GdCOGA GdegGQj GdMQcj dOi JdGejP GdeQMdI GdKGfhjI hfNU eMJhi GdJQHjI GdHOfjI hGdQjGVjI hdbO GSJYedfG aj gPg GdOQGSI GdefgL GdhUaj GdPj jYO GdGfSH Gdi gPg GdOQGSI, CeG eLJeY OQGSI bOQ H(B650 (3JdejP GNJQfG efge (B120 (3JdejP jeGQS GdfTGW GdHOfj GdQjGVj eY GSJHYGO GdJdGejP GdeYajjf ef MUI GdJQHjI GdHOfjI hGdQjGVjI hgPG dELQGA GdOQGSI GdCSGSjI, hbO GSJYedfG GSJHjGf OGaYjI GdCOGA Ydi GdJdGejP GdeeGQSjf ddfTGW GdQjGVj GdHOfj hGdQjGVj aj Xd GdeMJhi GdeOQS dOi JdGejP GdeQMdI GdKGfhjI, haj NJGe gPg GdOQGSI JhUdfG Gdi Cf daYGdjI hOhQ GdeMJhi GdeOQS CKQ cHjQ Ydi OGaYjI GdCOGA GdegGQj GdMQcj dOi JdGejP GdeQMdI GdKGfhjI hPdc ef NdGd Cf ddeMJhi GdeOQS dg GKQ Ydi eSJhi GdWehM aj GdCOGA GdegGQj GdMQcj dOi JdGejP GdeQMdI GdKGfhjI, ddeMJhi GdeOQS dg GKQ Ydi eSJhi GdeKGHQI aj GdCOGA GdegGQj GdMQcj dOi JdGejP GdeQMdI GdKGfhjI, ddeMJhi GdeOQS dg GKQ Ydi eSJhi GdCOGA aj GdCOGA GdegGQj GdMQcj dOi JdGejP GdeQMdI GdKGfhjI, ddeMJhi GdeOQS dg GKQ Ydi eSJhi GdJfGaS aj GdCOGA GdegGQj GdMQcj dOi JdGejP GdeQMdI GdKGfhjI, ddeMJhi GdeOQS dg GKQ Ydi eSJhi GOQGc GdRef aj GdCOGA GdegGQj GdMQcj dOi JdGejP GdeQMdI GdKGfhjI(B. (3GdcdeGJ GdeaJGMjI(B: (3GdefgGL(B- (3GdeMJhi GdeOQS(B- (3GdOGaYjI(B- (3GdCOGA GdegGQj GdMQcj(B- (3GdeQMdI GdKGfhjI(B. s
(3OcJhQGIs
Keywords: (3GdJYde h GdeQGbHI GdMQcjIs; (3GdOGaYjIs; (3Yde GdMQcIs